Combination system of slide variations of electric motors when using a probabilistic modelling approach of tractive effort distribution in multimotor drives of multidrive belt conveyors - Goncharov K.A. (Научно-технический вестник Брянского государственного университета)
The paper is aimed at specifying and summarizing system-wide and internal slide variations of electric motors in the structures of multimotor drives of multidrive belt conveyors. The accounting principle of the indicated variations is formulated in the form of the hierarchic structure when building a probabilistic mathematical model of tractive effort distribution in the multidrive belt conveyor. A system of the obligatory internal combinations of slide variations of electric motors in the multidrive belt conveyor is suggested. Taking into account the recommendations of the given system, the dependencies enabling one to estimate the labour coefficient of the probabilistic modelling and give detailed and qualitative descriptions of every design case are suggested.